Efek Abelmoschus esculentus terhadap Glukosa Darah, Superoksida Dismutase, dan Malondialdehid Rattus norvegicus Diabetes Melitus dengan Induksi Streptozotocin - Olivia Herliani (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2018)
In diabetes mellitus there is an increase in oxidative stress in which oxidants exceed the antioxidant system resulting from the production of oxidant-antioxidant imbalance and/or limited antioxidant defenses. Abelmoschus esculentus (“okra”) is known as lowering blood glucose vegetable by Indonesian. A. esculentus has a high antioxidant activity that can: 1) lower H2O2 level; 2) decrease the amount of ROS; 3) lower •OH level. This study tried to prove that administration of A. esculentus may decrease fasting blood glucose, serum malondialdehyde, and increase superoxide dismutase activity of diabetic male white rats. This research is a pure experimental research, with randomized post test only control group designs, held in 28 days. Thirty one rats were divided into 4 groups randomly: KN = normal control group given 0.1% Na-CMC solution; KDM = DM control group injected with STZ, followed by 0.1% Na-CMC solution; P1 = treatment group 1 injected with STZ, followed by administration of A. esculentus at a dose of 775 mg/kgBW/day; P2 = treatment group 2 injected with STZ, followed by administration of A. esculentus at a dose of 1550 mg/kgBW/day. The result: administration of A. esculentus at doses of 775 mg/kgBW/day and 1550 mg/kgBW/day can not decrease fasting blood glucose and MDA serum level of diabetic male white rats. Giving A. esculentus at a dose of 1550 mg/kgBW/day may increase the activity of SOD erythrocytes of diabetic male white rats.. Conclusions: A. esculentus has the potential to lower blood glucose and MDA serum levels, also increase erythrocyte SOD activity.